Determinación del Costo de Producción de Miel en la Empresa “API-LOJA” de la Ciudad de Loja, Periodo del 01 de abril al 30 de junio 2023. - Iñiguez Ayala, Karen Valeria (2024)
The Curricular Integration Work called "Determination of the Cost of the Production of Honey in the Company "API-LOJA" of the City of Loja, Period from April 1 to June 30, 2023", was carried out with the purpose of presenting a viable solution to the problem of the lack of a cost accounting organization in the company, which helps to determine the total and unit cost of the production of bee honey. For the development of the present work and the fulfillment of the proposed objectives, research methods and techniques were used. In the first objective, a plan and manual of accounts were designed and elaborated with their respective numbering according to the nature of the operations of the apiculture company, identifying the accounts of Assets, Liabilities, Estate, Revenues, Costs and Expenses, facilitating the recording of transactions. For the second objective, auxiliary records were developed to control the cost elements involved in the production process, the raw material is supported by the design of requisition notes, purchase requests, purchase orders, and Kardex cards for the control of inventories by means of a permanent control system; the elaboration of time cards for the control of the workforce and payment roles to obtain the monthly value that the workers receive; for indirect manufacturing costs, depreciation aids were made showing the residual values of fixed assets and consumption of inventories used in the honey production period. Finally, in order to implement the third objective, it was begun with the cost accounting process, preparing the initial inventory that reflects assets, rights and obligations at the beginning of the period, transferring the values to the Initial Situation Statement, to start with the records in the journal, the general ledger as a basis for structuring the balance sheet until the obtaining and presentation of the Financial Statements, consisting of the Statement of Financial Position, Statement of Results, Statement of Cash Flows, Statement of Production Costs and Explanatory Notes, obtaining sufficient and relevant information on the economic-financial situation of the company recording values of Assets for $204,212.01; Liabilities of $16,581.32; Assets of $187,630.69; Profit of $2,959.46 and Production Costs for $3,599.47, useful information for the owner since it facilitates management decisions based on their economic reality.